2012
DOI: 10.1111/j.1743-7563.2011.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Is advanced age a barrier to effective cancer treatment? The experience of nonagenarians receiving radiation therapy

Abstract: Nonagenarian patients receiving treatment had satisfactory tolerability and achieved expected survival rates post-RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…One reason for under-treatment could be due to clinicians' frequent underestimation of the life expectancy of the elderly; another could be limitations in economic resources. Additionally, the omission of the elderly from clinical trials and the subsequent lack of evidence for treatment of elderly patients have been criticised [18,29].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for under-treatment could be due to clinicians' frequent underestimation of the life expectancy of the elderly; another could be limitations in economic resources. Additionally, the omission of the elderly from clinical trials and the subsequent lack of evidence for treatment of elderly patients have been criticised [18,29].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for elderly GC patients has been criticized. 35 Factors such as comorbidity and decreased functional status may influence the selection of treatment strategies for elderly patients. One of the main concerns with gastrectomy in the elderly is palliative operation or radical dissection.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The limited number of existing publications often included low numbers of elderly patients 17 or were small, [14][15][16] included palliative treatments, [14][15][16] or were limited by short follow-up time. 16 The outcomes of our study may be affected by selection bias and inclusion of the "well" old; 70% of the patients in our study had an ECOG PS score of 0 or 1 and 72% had a CCMI score of 0. In contrast, a study of comorbid conditions in patients with breast cancer who were over the age of 80 years found that only 35% of patients were free of common comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%